Syntheses Based on 3,4α-Epoxy-1,5,7α,6β(H)-guai-10(14),11(13)-dien-6,12-olide - Sergazy Adekenov (Molecules, 2022)
The sesquiterpene γ-lactone estafiatin 1, the molecule of which has a structure of 3,4α-epoxy-1,5,7α,6β(H)-guai-10(14),11(13)-dien-6,12-olide, is characteristic of plants of the genera Achillea L. and Artemisia L. of the Asteraceae family. This article presents the results of chemical modification for three reaction centers of the estafiatin molecule 1: epoxy cycle, exomethylene group conjugated with γ-lactone carbonyl, and exomethylene group in position C10=C14; and at the same time 33 new derivatives were synthesized, the structures of which were established based on physicochemical constants, spectral data (IR-, PMR-, 13C-NMR), and X-ray diffraction analysis. The stereo- and regiospecificity, as well as the chemoselectivity of the reaction based on estafiatin molecule 1, are discussed. The reactivity of the substrate is significantly influenced by the stereochemistry of its molecule, the nature of the reagent, and the reaction medium. Based on the results of in silico screening, derivatives of estafiatin with high binding energies for both DNA-topoisomerase I and DNA-topoisomerase II were identified. The values of the inhibitory dose of IC50 for estafiatin 1 and its derivatives were determined on cell lines of eight types of tumors. in vivo experiments of the samples made it possible to establish that estafiatin 1 and its derivatives have pronounced antitumor activity against Pliss lymphosarcoma, Walker’s carcinosarcoma, sarcoma 45, sarcoma-180, alveolar liver cancer PC-1, leukemia P-388 and L-1210, and sarcoma-45 resistant to 5-fluorouracil.